Preliminary study on the neural mechanisms of four tone recognition in deaf children using fMRI - Qiang Li; Yuan Meng; Qiuli Li; Heng Zhao; Shiyu Li (Scientific Reports)
Abstract Vocal intonation, a fundamental element of speech, is pivotal for comprehending and communicating effectively. Nevertheless, children suffering from hearing impairment encounter difficulties in recognizing vocal intonation patterns, primarily stemming from their auditory deficits. In 2020, a study conducted at Tianjin Medical University General Hospital in Tianjin, China, recruited five deaf children and two children with normal hearing (male; mean age = 10.21 ± 0.4 years) to compare the differences between deaf and normal children in four Chinese tone recognition tasks. The results revealed that (1) Due to hearing loss, some of the auditory cortices responsible for processing vocal intonation in deaf children do not function optimally, (2) When decoding vocal intonation information, deaf children might utilize alternative neural pathways or networks, (3) Deaf children exhibit hemispheric specialization in their processing of vocal intonation cues.